Distribution of root activity in young' Alphonso' mango (Mangifera indica) trees as influenced by season and growth - KOTUR, S C; IYENGAR, B R V; SHIVANANDA, T N (The Indian Journal of Agricultural Sciences, 2013)
Spatial distribution of root activity was studied using 32p     soil injection technique in 8-year-old' Alphonso' mango(Mangifera indica L.) budded on 'Bangalora' rootstock    grown on a loamy sand (Typic Haplustalf) belonging to'Thyamagondlu' series. During the Jate rainy season the   bulk of the active roots (80%) was confined to 100 cm radialdistance, out of which 30% was found at 50 cm distance. Substantial percentage of active roots was found at 20 and  60 cm depths (41 and 46% respectively), whereas only 12% active roots occurred at 40 cm depth. During winter the bulk of the root activity (80-85%) was found uniformly distributed up to 100 cm lateral distance. The root activity increased with depth. In summer only 20 and 28% active roots were found at 50 and 100 cm lateral distances, whereas 52% active roots were found at 150 cm distance. Root activity decreased with depth (50,31 and 19% at 20, 40 and 60 cm respectively). There was variation in the distribution of active roots with season, indicating that high root activity coincided with high volumetric moisture content in the soil profile, particularly in the top 15 cm layer. The high intensity' of root activity preceded a period of high shoot and floral growth observed in winter. In summer the root activity was very low. The presence of significant root acitivity (40 - 70%) below 20 cm depth despite clayey texture, hard to very hard dry consistency and blocky structure was probably due to the presence of adequate moisture at these depths.